A Maker of Useful Images. The “Litografia del Estado of Buenos Aires” between Republicanism and Market Economy (1829-1838) - Steardo, Mattia (Confluenze. Rivista di Studi Iberoamericani, 2022)
This paper analyses the activities of the Bacle lithography in Buenos Aires, and its ambivalent relationship with the governments of Juan Manuel de Rosas. This story is read in the light of two wider phenomena that were affecting the Atlantic world, namely the diffusion of new forms of visual politicisation linked to republicanism and the construction of interconnected and interdependent market economies. The lithography permitted and was sustained by the two aforementioned processes.